1994
DOI: 10.2214/ajr.163.6.7992747
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of recurrent brain tumor: value of 201Tl SPECT vs 18F-fluorodeoxyglucose PET.

Abstract: OBJECTIVE.This prospective study was designed to compare the sensitivity and specIficity of a relatively simple examination, We were unable to detect a statistically significant difference in sensitivity or specificity between the 201T1 SPECT and FDG PET scans. Both techniques were sensitive for tumor recurrence with lesions less than 1.6 cm or larger. However, given the greater availability, simplicity, and ease of interpretation and the lower cost of the 201TI SPECT studies, this technique should be conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
1
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(53 citation statements)
references
References 4 publications
(4 reference statements)
1
49
1
2
Order By: Relevance
“…But later studies, in 1990's, showed that value of this technique in distinguishing between post-therapeutical changes and brain tumor recurrences could be limited, because of lower specificity. [20,21,22] Recent studies have reported the sensitivity and specificity of 18 FDG/PET in differentiation of radiation injury from tumor recurrences between 81% to 100 % and 40% to 100 % respectively, greatly depending on primary tumor pathologic grade. Causes of false-positive results include recent radiation therapy, nonmalignant inflammatory processes and subclinical seizure activity.…”
Section: Discussionmentioning
confidence: 99%
“…But later studies, in 1990's, showed that value of this technique in distinguishing between post-therapeutical changes and brain tumor recurrences could be limited, because of lower specificity. [20,21,22] Recent studies have reported the sensitivity and specificity of 18 FDG/PET in differentiation of radiation injury from tumor recurrences between 81% to 100 % and 40% to 100 % respectively, greatly depending on primary tumor pathologic grade. Causes of false-positive results include recent radiation therapy, nonmalignant inflammatory processes and subclinical seizure activity.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigating the potential of 18 F-FDG in discriminating tumor recurrence and RN have been performed. However, equivocal results with sensitivities and specificities ranging from 40 to 100% were published (21,28,34,(46)(47)(48). Besides the high and variable uptake by the normal cortex, radiation injury can activate repair mechanisms or lead to inflammation, which can lead to false-positive results (20).…”
Section: Pet For Therapy Response Assessment In Gbmentioning
confidence: 99%
“…Finally, 18 F-FCho PET was assumed to be promising in differentiating GB from RN (47,52,97). 18 F-FCho PET was studied in patients with solitary brain lesions and correctly identified patients with RN based on LNR (87).…”
Section: F-fluoromethylcholine ( F-fcho)mentioning
confidence: 99%
“…[4] Functional imaging with thallium-201 (Tl-201) single-photon emission computerized tomography (SPECT) has recently been reported to be useful in predicting the presence and location of recurrent brain tumor after debulking and radiation treatment. [1,15,16,21,22,29,35] This technique has been found to be equal in accuracy to fluorine-18 deoxyglucose positron emission tomography for this purpose. [1,15] The radioisotope Tl-201 is a potassium analog that requires a disrupted blood-brain barrier (BBB) to gain access to the brain and is then taken up in proportion to the activity of the sodium-potassium adenosine triphosphatase pump.…”
mentioning
confidence: 96%
“…[1,15,16,21,22,29,35] This technique has been found to be equal in accuracy to fluorine-18 deoxyglucose positron emission tomography for this purpose. [1,15] The radioisotope Tl-201 is a potassium analog that requires a disrupted blood-brain barrier (BBB) to gain access to the brain and is then taken up in proportion to the activity of the sodium-potassium adenosine triphosphatase pump. Previous reports that analyzed survival as a function of Tl-201 uptake in small populations did not analyze either the pattern of recurrence or the original tumor grade.…”
mentioning
confidence: 96%